2017
DOI: 10.3791/56626
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Workflow for the Genome-wide Identification and Expression Meta-analysis of the ATL E3 Ubiquitin Ligase Gene Family in Grapevine

Abstract: Classification and nomenclature of genes in a family can significantly contribute to the description of the diversity of encoded proteins and to the prediction of family functions based on several features, such as the presence of sequence motifs or of particular sites for post-translational modification and the expression profile of family members in different conditions. This work describes a detailed protocol for gene family characterization. Here, the procedure is applied to the characterization of the Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…E3 ubiquitin ligases have been reported to function in several processes, including the responses to biotic and abiotic stresses ( Ariani et al, 2017 ; Sun et al, 2019 , 2022 ; Zhang et al, 2019 ; Du et al, 2021 ; Sharma et al, 2021 ). First, E3 ubiquitin ligases are involved in response to biotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…E3 ubiquitin ligases have been reported to function in several processes, including the responses to biotic and abiotic stresses ( Ariani et al, 2017 ; Sun et al, 2019 , 2022 ; Zhang et al, 2019 ; Du et al, 2021 ; Sharma et al, 2021 ). First, E3 ubiquitin ligases are involved in response to biotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…We previously described a small group of grapevine genes encoding RING-H2 E3 ubiquitin ligases that were more strongly or specifically expressed in the resistant species Vitis riparia than its susceptible relative V. vinifera following infection with P. viticola [ 17 ]. All these genes belong to the ATL subfamily, associated with defense in Arabidopsis thaliana and other species [ 18 , 19 , 20 , 21 , 22 ]. Following extensive characterization of the grapevine ATL gene family and meta-analysis of the transcriptome datasets, we found that the expression of these genes is induced in response to a range of pathogens [ 20 ] and co-regulated together with key components of the resistance signaling cascade [ 22 ].…”
Section: Introductionmentioning
confidence: 99%